Private and Public Islam: Social Behaviour of Indonesian Muslim in Facing Covid-19 - Halim, Abdul (Jurnal Komunikasi Islam, 2021)
This article reports on a library research regarding the behaviour changes of Indonesian muslim resulted from the Covid 19 pandemic. Using Henri Lefebvre’s theory of public space, this study has found that, first, the changing of social-diversity that creates a new space dimension, it is the private space; second, the behaviour of social-diversity in private space showed the pattern of Islamic hyper-locality which is a form of Islam Locality with its different attribute and character; third, Islamic hyper-locality leads any confrontation of muslim groups who want to beg the public space and its religious activities; forth, the distortion of the value of Universal Islam and uncapability in facing the global war.